Sociology in focus : for AQA A2 level - Haralambos, Michael; Langley, Peter, 1954- (Ormskirk : Causeway, 2004)
'Sociology in Focus' covers the most popular topics in the AQA A2 specification: religion, power and politics, theory and methods, and crime and deviance. Each chapter contains a range of interesting activities which allow student to apply and develop ideas from the preceding text.
Includes bibliographical references (p. 275-281) and index.
Keywords: Sociology; Society